Implementasi Pendidikan Karakter Berbasis Kearifan Lokal Madura untuk Mewujudkan Generasi Toleran - Hanaris, Fitria (Proceedings of Annual Conference for Muslim Scholars, 2025)
This study focuses on the implementation of character education based on Madurese local wisdom at SMPIT Mutiara Ilmu Bangkalan. The research aims to describe how local cultural values are integrated into school activities to develop tolerant and religious students. This study employed a qualitative case study method, collecting data through interviews, observations, and document analysis. The findings show that the values of “buppa’, babbu’, guru, rato’” are embedded through religious, social, and cultural activities, such as congregational prayers, Friday charity, community service, and the use of polite Madurese language. These practices have strengthened students’ discipline, religiosity, social awareness, and tolerance. The discussion reveals that habituation and teacher exemplarity are key to internalizing these values, aligning with Lickona’s and Bourdieu’s theories of moral and cultural formation. In conclusion, Madurese local wisdom-based character education effectively nurtures tolerant, ethical, and culturally rooted students.